Addressing stigma within the dissemination of research products to improve quality of care for pregnant and parenting people affected by substance use disorder - Lipsett, Megan; Wyant-Stein, Katie; Mendes, Simone; Berger, Estelle; Berkman, Elliot T.; Terplan, Mishka; Cioffi, Camille C. (Frontiers in Psychiatry, 2023)
Substance use disorders are a common and treatable condition among pregnant and parenting people. Social, self, and structural stigma experienced by this group represent a barrier to harm reduction, treatment utilization, and quality of care. We examine features of research dissemination that may generate or uphold stigmatization at every level for pregnant and parenting individuals affected by substance use disorder and their children. We explore stigma reduction practices within the research community that can increase uptake of evidence-based treatment programs and prevent potential harm related to substance use in pregnant and parenting people. The strategies we propose include: 1) address researcher stereotypes, prejudice, and misconceptions about pregnant and parenting people with substance use disorder; 2) engage in interdisciplinary and transdisciplinary collaborations that engage with researchers who have lived experience in substance use; 3) use community-based approaches and engage community partners, 4) address stigmatizing language in science communication; 5) provide contextualizing information about the social and environmental factors that influence substance use among pregnant and parenting people; and 6) advocate for stigma-reducing policies in research articles and other scholarly products.